2015
DOI: 10.1002/eco.1683
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting retention of nutrients and organic matter in stormwater ponds

Abstract: Stormwater ponds are a common way to handle urban runoff. Different pond designs have been tested for decades to retain as much water as possible. Lately also, retention of nutrients and organic matter has become increasingly important, to reduce the eutrophication of downstream aquatic systems and thereby, e.g. fulfil the European Water Framework Directive. We have examined the load of particulate and dissolved fractions of organic matter, phosphorus, nitrogen and iron in 66 Danish ponds to determine the impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 26 publications
2
33
0
Order By: Relevance
“…The remaining papers deal with the use of SWEs as biogeochemical reactors, able to ensure the achievement of good ecological status (as imposed by WFD) of related/connected larger water ecosystems (included in the WFD) at the basin scale, both in urban (as stormwater ponds) [47][48][49] and rural contexts [50][51][52][53]. The potential role of SWEs in controlling N and P retention was extensively explored, especially in Northern Europe (Denmark, Sweden, Norway), although more data is needed to better evaluate the effects of hydrologic pulsing on wetland metabolism and performance in the mid to long-term [50].…”
Section: Swes In the Frame Of The Wfd Implementationmentioning
confidence: 99%
“…The remaining papers deal with the use of SWEs as biogeochemical reactors, able to ensure the achievement of good ecological status (as imposed by WFD) of related/connected larger water ecosystems (included in the WFD) at the basin scale, both in urban (as stormwater ponds) [47][48][49] and rural contexts [50][51][52][53]. The potential role of SWEs in controlling N and P retention was extensively explored, especially in Northern Europe (Denmark, Sweden, Norway), although more data is needed to better evaluate the effects of hydrologic pulsing on wetland metabolism and performance in the mid to long-term [50].…”
Section: Swes In the Frame Of The Wfd Implementationmentioning
confidence: 99%
“…These small ponds remove nutrients by way of particle sedimentation, physical absorption, and uptake by resident biota, all of which could improve water quality downstream (Comings et al, 2000). While promoted as a possible nutrient sink (Brunberg & Boström, 1992;Maavara et al, 2015), stormwater ponds have been found to have highly variable (10-90%) and generally quite low (average~30-40%) retention efficiencies of P (Gold et al, 2017a(Gold et al, , 2017bSonderup et al, 2016). Variable and generally low retention efficiency of P in urban stormwater ponds may be partly explained by internal pond P biogeochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…interestingly Sønderup et al (2016) found that when comparing P, N, and Fe removal efficiency of stormwater ponds, the ponds which were greater than 10 years old demonstrated no retention capabilities for particulate or dissolved constituents. This suggests that regular maintenance of ponds is critical and that decreases in performance should be considered when modeling future behavior.…”
Section: Constructed Stormwater Pondsmentioning
confidence: 99%